Efektivitas Dosis Vermikompos dan Jenis Mikoriza Terhadap Pertumbuhan Dan Hasil Tanaman Kedelai (Glycine max L. Merril) Pada Tanah Ultisol Jantho - Cut Nina Herlina; Syafruddin Syafruddin; Zaitun Zaitun (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
Vermicompost Doses and Mycorrhiza Types Effectivity to Growth and Yield of Soybean (Glycine max L. Merril) on Jantho`s UltisolABSTRACT. This study aims to determine the effect of multiple doses of vermicompost and types of mycorrhiza on the gowth and yield of soybean in Jantho`s Ultisol. The experiment was conducted at the screen house in the Office of Assessment Institute for Agricultural Technology (AIAT) Aceh. The research was conducted from June to September 2014. The method used in this study is the experimental method with pot experiment using a factorial randomized block design with three replications. Vermicompost doses consists of 4 levels: 0, 50, 100 and 150 g pot-1. Giving FMA consists of: without mycorrhiza, 50 g pot-1 (Gigospora decipien) and 50 g pot-1 (Glomous mosseae). The study consisted of 12 combinations. Variables measured include: the response of plants (plant height, stem diameter, number of pods, number of seeds per plant, seed weight per plant, weight per 100 seeds, stover weight of fresh and dry stover, fresh root weight and root dry). The results showed that the best combination treatment is dose of vermicompost 150 g pot-1 with mycorrhizal Glomous mosseae.